2001
DOI: 10.1176/appi.ajp.158.10.1617
|View full text |Cite
|
Sign up to set email alerts
|

Does Thyroid Supplementation Accelerate Tricyclic Antidepressant Response? A Review and Meta-Analysis of the Literature

Abstract: This meta-analysis supports the efficacy of T(3) in accelerating clinical response to tricyclic antidepressants in patients with nonrefractory depression. Furthermore, women may be more likely than men to benefit from this intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
107
3
5

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(123 citation statements)
references
References 43 publications
4
107
3
5
Order By: Relevance
“…Only women were studied here because previous work has indicated that women benefit more than do men from thyroid hormone supplementation. [39][40] On the basis of previous findings from functional PET studies in bipolar depression, we hypothesized that patients with bipolar depression would have lower relative activity in the middle frontal gyri (within the DLPFC) 35 and the region described by Drevets et al 34 as subgenual prefrontal cortex (here renamed more descriptively as the subgenual cingulate cortex), and higher activity in subcortical and limbic structures 36 compared to healthy controls. We further hypothesized that adjunctive L-T 4 treatment would improve mood in bipolar depressed patients, and that clinical improvement would be associated with increased activity in the prefrontal cortex and decreased activity in limbic and subcortical structures, including the basal ganglia and thalamus.…”
mentioning
confidence: 99%
“…Only women were studied here because previous work has indicated that women benefit more than do men from thyroid hormone supplementation. [39][40] On the basis of previous findings from functional PET studies in bipolar depression, we hypothesized that patients with bipolar depression would have lower relative activity in the middle frontal gyri (within the DLPFC) 35 and the region described by Drevets et al 34 as subgenual prefrontal cortex (here renamed more descriptively as the subgenual cingulate cortex), and higher activity in subcortical and limbic structures 36 compared to healthy controls. We further hypothesized that adjunctive L-T 4 treatment would improve mood in bipolar depressed patients, and that clinical improvement would be associated with increased activity in the prefrontal cortex and decreased activity in limbic and subcortical structures, including the basal ganglia and thalamus.…”
mentioning
confidence: 99%
“…Another meta-analysis by Altshuler et al [33] found that in five of six studies, T3 was significantly more effective than placebo in accelerating clinical response to TCAs in nonrefractory depression (weighted effect size index = 0.58). They also found that women were more likely than men to benefit from this strategy.…”
Section: Level 2: Triiodothyroninementioning
confidence: 99%
“…Thyroid hormones (TH) have a profound influence on behavior and mood, and appear to be capable of modulating the phenotypic expression of major affective illness 3,4,5,6 . Thyroid supplementation is now widely accepted as an effective treatment option for patients with affective disworders 7,8,9 .…”
mentioning
confidence: 99%